Self-incompatibility in plums (Prunus salicina Lindl., Prunus cerasifera Ehrh. and Prunus domestica L.). A minireview - Hegedűs, A.; Halász, J. (International Journal of Horticultural Science, 2006)
Japanese plums (P salicina) and cherry plums (P cerasifera) are diploid species, while European plum (P. domestica) cultivars are hexaploids. Most diploid species are self-incompatible while fertility relations of the hexaploid European plums are variable between self-incompatibility and self-compatibility. About twenty S-alleles and six inter-incompatibility groups and one S-haplotype responsible for the self-fruitful phenotype were described in Japanese plum cultivars, but studies on cherry plums and even on the European plum cultivars are severely restricted. This review is focused on the available information obtained from myrobalans and European plums; and discusses recent hypotheses regarding the putative origin of the hexaploid plums, and thereby indicates the possibility of allele flow between different plum species.